Hands in clay - Speight, Charlotte F., 1919-; Toki, John. (Boston : McGraw-Hill, 2004)
This is the only full four-color introductory ceramics text available that combines a thorough appreciation of the aesthetics of ceramic art with extensive discussions of the history of ceramics as well as techniques for working in clay.
Part 1: Shaping the past -- Chapter 1: An introduction to clay -- Chapter 2: Early Western Asia and the Mediterranean -- Chapter 3: Asia -- Chapter 4: Africa -- Chapter 5: Indigenous America -- Chapter 6: Europe -- Chapter 7: The United States -- Chapter 8: Worldwide interaction -- Part 2: Shaping the present -- Chapter 9: The artist's vision -- Chapter 10: Getting to work with clay -- Chapter 11: Handbuilding -- Chapter 12: Throwing on the wheel -- Chapter 13: Molds -- Chapter 14: Texture, color, and glaze -- Chapter 15: Firing -- Chapter 16: Installations and architectural works -- Chapter 17: Setting up your studio.
Includes bibliographical references and index.
Keywords: Pottery craft; Pottery craft